2018
DOI: 10.1137/17m1119020
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Gauge and Perspective Duality

Abstract: We revisit the foundations of gauge duality and demonstrate that it can be explained using a modern approach to duality based on a perturbation framework. We therefore put gauge duality and Fenchel-Rockafellar duality on equal footing, including explaining gauge dual variables as sensitivity measures, and showing how to recover primal solutions from those of the gauge dual. This vantage point allows a direct proof that optimal solutions of the Fenchel-Rockafellar dual of the gauge dual are precisely the primal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…When comparing to AVE, the research associated to AVO problems is insufficient and one of these reasons is the difficulty for obtaining feasible solutions of the problems. In fact, their constraints include AVE, which are known to be NP-hard [14].Another optimization problem that is related to AVO was recently investigated by Friedlander et al [8] and Aravkin et al [2]. It is called gauge optimization, which basically consists in an optimization problem with the so-called gauge function.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…When comparing to AVE, the research associated to AVO problems is insufficient and one of these reasons is the difficulty for obtaining feasible solutions of the problems. In fact, their constraints include AVE, which are known to be NP-hard [14].Another optimization problem that is related to AVO was recently investigated by Friedlander et al [8] and Aravkin et al [2]. It is called gauge optimization, which basically consists in an optimization problem with the so-called gauge function.…”
mentioning
confidence: 99%
“…However, differently from AVO, this problem does not consider multiple constraints, but only one gauge constraint. In [2,8], the authors showed that the Lagrange dual of gauge optimization problems can be written in a closed-form by using the polar of the gauge functions.In this paper, similarly to [2,8], we introduce a generalized AVO problem, and show that it has a wider practical application comparing to AVO problems. It is also more general than gauge optimization problems, because multiple constraints can be considered here.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, each atom is a subgradient of σ A . The theoretical basis for this approach is outlined by Friedlander et al [8] and Aravkin et al [9].…”
Section: Dual Atomic Pursuitmentioning
confidence: 99%